Comparative thermal decomposition kinetic analysis of the biodegradable terpolymer poly(lactide-co-propylene carbonate) applied by various theoretical models. (October 2018) - Huang, Guojia; Lin, Jinmei; Yang, Bo; Li, Maodong; Li, Yujie; Zhai, Wei; Wang, Zhigang; Li, Guanbao; Li, Lushui
Abstract: The thermal stability and non-isothermal decomposition kinetics of the terpolymer poly (lactide-co-propylene carbonate) (PLAPC) were studied by thermogravimetric and derivative thermogravimetric analyses with multiple heating rates (2.5, 5, 10, 20 °C min −1 ) under nitrogen gas atmosphere. The microstructure and molecule thermal transition property of PLAPC were examined by 1 H NMR, FTIR and differential scanning calorimetry (DSC) respectively. The decomposition kinetic parameters of PLAPC were calculated using ''model-free'' integral method (Flynn-Wall-Ozawa), ''model-free'' differential method (Kissinger) and ''model-fitting'' method (Tang). Its average activation energy thus obtained with different methods ranges from 96.62 to 104.91 kJ mol −1 12 kinetic models were employed to check the most probable decomposition mechanism. The results showed R2 model, F1 (A1) model and R3 model are the most probable to fit the decomposition mechanism. Highlights: Thermal decomposition parameters of poly(lactide-co-propylene carbonate) were evaluated using ''model-free'' differential method, ''model-free'' integral method and ''model-fitting'' method. 12 comparative models were used to analyze the decomposition mechanism of poly(lactide-co-propylene carbonate). R2 cylinder symmetry mechanism was considered as the most suitable for poly(lactide-co-propylene carbonate). Tang method is the best to descript the decomposition kinetic of poly(lactide-co-propylene carbonate).